Economic restructuring, human rights, state security and democratic viability in Trinidad and Tobago. - GRIFFIN, Clifford E. (1995)
Hypothesizes a relationship between the type of development strategy that a country pursues, the extent to which that strategy fosters or restricts support for human rights, and the implications that support (or lack thereof) for human rights may have for democratic governance and state security. Focuses on Trinidad and Tobago as the unit of analysis.